Continuous venovenous hemofiltration decreases mortality and ameliorates acute lung injury in canine model of severe salt water drowning. Issue 1 (December 2016) - Chen, Jian; Chen, Guangming; Xiao, Daping; Peng, Weihua; Yu, Guoqing; Lin, Yueyong; Zheng, Feng
Abstract Background Pulmonary edema is an important cause of complications and death in severe drowning. Continuous veno-venous hemofiltration (CVVH) may reduce pulmonary edema and thus may be a treatment modality for severe sea water drowning resuscitation. Methos 20 dogs were anesthetized and tracheally intubated. 10 ml/kg of sea water was infused into trachea in a minute. All animals developed signs of respiratory distress and severe hypoxia (PaO2  < 40 mmHg) within 15 minutes after infusion. They were then mechanical ventilated and randomized to receive either CVVH (n  = 10) or no additional treatment (control, n  = 10) and followed over 4 hours. Arterial gas, hemodynamic parameters, and the levels of circulating inflammatory cytokines including interleukin 6 (IL-6), interleukin 8 (IL-8), and tumor necrosis factor α (TNFα) were determined. Additionally, blood endothelin and the levels of oxidative stress in lung were measured at sacrifice. Results 5 animals in the control group (50 %) died within 4 hours after sea water aspiration, while 10 animals received CVVH all survived (p  < 0.05). Importantly, CVVH significantly improved blood gas exchange as evidenced by higher PaO2, normal oxygen saturation, and no carbon dioxide retention after 3 hour of CVVH, while also correcting against acidosis. Levels of circulating IL-6, IL-8, and TNFα were elevated in control but not in CVVH group (p  < 0.01). CVVH also reduced plasma endothelin and alleviated oxidative stress. Histology examination further revealed reductions in pulmonary alveolar injury, blood congestion, and inflammation by CVVH. Discussion and conclusions CVVH decreased mortality and pulmonary injury and largely maintained hemodynamic and acid-base balance in animals with severe sea water drowning and thus, may be added as a new measure to aid in resuscitation from severe sea water drowning. Trial registration Animal protocol number: FZG0001859http://www.fzzyy.com .